The Impact of Anesthesia Method on Postoperative Cognitive Functions in Urological Surgeries: A Prospective Randomized Single-Blind Study - Nurettin Kurt (Van Tıp Dergisi, 2023)
INTRODUCTION: Postoperative cognitive dysfunction contributes to cognitive impairments following surgeries.Despite the potential of anesthesia methods causing cognitive dysfunction,conclusive evidence remains elusive.This study aims to compare the effects of general and spinal anesthesia on postoperative cognitive functions in patients undergoing urological surgeries. METHODS: 108 patients aged 18 to 75 years, who underwent elective surgeries,were included in this study.Regardless of the anesthesia method chosen for surgery, the Mini-Mental State Test (MMST) was administered by a clinician at 24 hours preoperatively to assess cognitive functions in a blinded manner. At postoperative 24 hours, the same independent clinician repeated the MMST assessment. Preoperative and postoperative MMST scores were recorded. Patients were categorized into two groups: Group G received general anesthesia,and Group S underwent spinal anesthesia.Demographic data,surgery durations,and MMST values of the included cases were compared between the groups. RESULTS: Of the 108 included patients, 80 were male (74.1%) and 28 were female (25.9%). Forty-eight patients received general anesthesia (Group G), while 60 patients received spinal anesthesia (Group S).No significant differences were observed between the groups in terms of age,ASA classification,and comorbidities.The female-to-male ratio was statistically significantly higher in Group G,while the male-to-female ratio was higher in Group S (p=0.014). The average surgery duration in Group G (87.56+-28.15 minutes) was significantly longer than that in Group S (61+-18.91 minutes) (p=0.001).When comparing preoperative and postoperative 24-hour MMST scores in both groups,no statistically significant differences were observed. DISCUSSION AND CONCLUSION: No significant differences were found in terms of postoperative cognitive dysfunction between the general and spinal anesthesia methods used in patients undergoing urological surgeries